Sistema de depreciacion basado en la actividad del activo fijo productivo para el sector camaronero. - Mendez Valiente, Alvaro Mauricio (My University, 2021)
This research work refers to the use of depreciation by the accelerated method, considering the estimated working hours issued by the supplier for each fixed asset used in the agricultural sector. This procedure allows measuring with greater accuracy the cost for this concept that can be used as a deductible expense in the income tax return and therefore be timelier when making decisions for new investments in the equipment required in the production of the shrimp sector. In Chapter I, the basic aspects of the research are considered, such as the object, justification and objectives that guide its actions for the development of the problem. The object of study considered for this research are the shrimp companies in the Santa Rosa canton where viable and reasonable information will be obtained on how they carry out the treatment of depreciation for their fixed assets. Also, we will know what has been the development of the shrimp sector from its beginnings to the present, then we will justify the investigation of the theory with the reality to be able to raise the objectives in relation to the problem of the investigation. In Chapter II, the theoretical references that have been considered from indexed publications in order to give greater scientific and theoretical rigor to the data presented. With this we will be able to argue on the basis of laws, norms, regulations and other legal instruments so that the research is supported by a good legal framework. In Chapter III, there is the methodology that has been used precisely to comply with the expectations raised with the purpose of evidencing the whole research process, applying the necessary tools so that the results obtained are reliable. This leads to the development of the problem using the necessary research methods that allow the application of a depreciation method that is accelerated by the tax administration. The development of the research is feasible as long as it finds the support of the entities of the shrimp sector, because accounting data will be obtained to perform the calculations of the accelerated depreciation method and the results obtained in the first instance can be compared. The application of a new depreciation methodology in the shrimp sector companies will show that there are new alternatives to know the real wear and tear of the assets and to be able to make good decisions. On other occasions there are companies that continue to depreciate their fixed assets without knowing that they are no longer in their place of work or that their useful life in the field has ended. Finally, in Chapter IV, the results show that there is a considerable difference in the use of the percentages estimated by the tax administration through its Regulation to the Internal Tax Regime Organization Law and therefore requires a specific analysis of each company to consider which of them best suits its needs. That is why the appropriate depreciation methods should always be used in relation to the laws, regulations, standards or other legal framework stipulated in our country or that governs worldwide. Sometimes there are companies in the shrimp sector that continue to depreciate their fixed assets without knowing that they are no longer operational due to lack of communication or information provided within the entity.
El presente trabajo investigativo hace referencia a la utilización de la depreciación por el método acelerado, considerando las horas de trabajo estimadas que emite el proveedor por cada activo fijo utilizado en el sector agropecuario, este procedimiento permite medir con mayor fidelidad el costo por este concepto que puede ser utilizado como gasto deducible en la declaración del impuesto a la renta y por consiguiente ser más oportuno al momento de tomar decisiones de nuevas inversiones en los equipos que se requiere en la producción del sector camaronero. En el Capítulo I, se consideran los aspectos básicos de la investigación como el objeto, justificación y objetivos que orientan su accionar para el desarrollo de la problemática. El Objeto de estudio que se consideró para esta investigación son las empresas camaroneras se cantón Santa Rosa en donde se obtendrá información viable y razonable de cómo realizan el tratamiento de depreciación para sus activos fijos. También, conoceremos cual ha sido el desarrollo del sector camaronera desde sus inicios hasta la actualidad, luego justificaremos la investigación de la teoría con la realidad para poder plantear los objetivos en relación a la problemática de la investigación. En el Capítulo II, los referentes teóricos que han sido considerados de publicaciones indexadas con el propósito de darle mayor rigor científico y teórico a los datos presentados. Con esto podremos argumentar en base a las leyes, normas, reglamentos y otros instrumentos legales para que la investigación se encuentre respaldada por un buen marco legal. En el Capítulo III, se encuentra la metodología que ha sido utilizada precisamente para dar cumplimiento a las expectativas planteadas con la finalidad de evidenciar todo el proceso investigativo, aplicando las herramientas necesarias para que los resultados obtenidos sean fidedignos. Esto conlleva al desarrollo de la problemática utilizando los métodos de investigación necesarios que permitan aplicar un método de depreciación que es acelerado por la administración tributaria. El desarrollo de la investigación es factible siempre y cuando halla el respaldo de las entidades del sector camaronero, porque se obtendrán datos contables para realizar los cálculos del método de depreciación acelerado y se podrán comparar los resultados obtenidos en primera instancia. La aplicación de una nueva metodología de depreciación en las empresas del sector camaronero, permitirá evidenciar que existen nuevas alternativas para conocer el desgaste real de los activos y puedan tomar buenas decisiones. En otras ocasiones hay empresas que siguen depreciando sus activos fijos sin conocer que ya no se encuentran en su lugar de trabajo o culmino su vida útil en campo. Finalmente en el capítulo IV, en los resultados se destaca que existe una diferencia considerable en el uso de los porcentajes que estima la administración tributaria a través de su Reglamento a la Ley Organiza de Régimen tributario Interno y por lo tanto requiere de un análisis específico de cada empresa, para considerar cuál de ellos se ajusta mejor a sus necesidades. Es por ello que siempre se debe utilizar las los métodos de depreciación adecuados en relación a lo que dictaminan las leyes, reglamentos, normas u otros marco legal estipulado en nuestro país o que rija a nivel mundial. En ocasiones hay empresas del sector camaronero que siguen depreciando sus activos fijos sin conocer que los mismos ya no se encuentran operativos por falta de comunicación o información proporcionada dentro de la entidad.
Keywords: DEPRECIACIÓN; ACELERADO